Mass rearing beneficial insects and the renaissance of biological control - Leppla, Norman C.; Williams, David W. (Pesquisa Agropecuaria Brasileira, 1992)
It is possible to mass rear hosts efficiently and reliably for the in vivo production of natural enemies. This can be cost effective even if the arthropod hosts must be reared on plants, as in the production of predaceous mites. Host mass rearing has been widely used to produce parasites and predators for both inoculative and inundative release. The use of natural enemies has been particularly successful where pesticides have proven ineffective due to pest distribution and resistance, and when natural enemies are preferred because of cost or the lack of environmentally-acceptable chemicals. There is little doubt that biological control is being reemphasized as environmental awareness increases, and more effort is required to prevent disease transmission and produce food. For biological control to achieve its potential, however, a new infrastructure must be developed that extends from support for basic research through successful application, documentation and adoption. The National Biological Control Institute was founded to help build this infrastructure and provide a catalyst for creating the associated new technologies. The way to accomplish this synthesis is to incorporate biological control into IPM systems, complete the research required to deploy alternative control tactics, and provide expertise for their implementation.